Body weight reduction in combat sports - Coufalová, K.; Prokešová, E.; Malý, T.; Heller, J. (Archives of Budo, 2013)
Competitions in combat sports are based on direct fight of competing parties. Weight limits in individual weight categories, are formal conditions for admitting to compete. Therefore, competitors are obliged to adapt their body weight to a particular weight category in a given time. The aim of this study was to knowledge about methods, including the length and other details of weight loss in combat sports with weight categories. Material & Methods: The study included 53 experienced athletes (37 men and 16 women) competing in judo, wrestling Greco-Roman and freestyle, kickboxing, karate, box, thai box and taekwondo. The athletes practiced combat sports in average 14.9 ± 4.4 years. Participants responded to a battery of questions (created by an experts), which was focused on personal information (e.g. age, sex, combat sport, length of sport practice, weight category and successes), reduction process (number of reductions per year, weight monitoring, using supplements, problems during weight reduction, etc.), methods of weight reduction and sources of information. Results: The results showed that 77.4 % of the participants regularly reduce their weight before competition and this reduction comprises in average 5.4 % of body weight (average body loss was 3.9 ± 2.3 kg, range from 1 kg to 10 kg). The most commonly applied body weight reduction methods included reduced food and liquids intake, diet changes, increased sweating and increased physical activity for higher energy output. Conclusions: The body weight reduction prior to competitions turned out to be a common practise. The rapid body weight reducing methods can negatively influence sport performance and also athlete`s health. Finding the most common ways of weight reduction is the first step to remedy inadequate procedures for body weight reduction.